Improving the Computer Literacy of Teachers and Students of Semarang City Elementary School - Widhanarto, Ghanis Putra; Prihatin, Titi; Haryono, Haryono; Kusumawardani, Seftia (Universitas Negeri Semarang, 2023)
Public spaces have been prepared for technology-literate human resources. Technology is synonymous with computerized operations, even all applications can be developed through computer devices. This ability is needed to keep pace with the development of technological innovation around the world. Central Java has great potential in contributing to the increase in computerization understanding scores for school students. The target elementary school is considered appropriate, because from the study of developmental psychology has proven that elementary school students are most appropriately taught early talents and interests. This service aims to improve the ability of teachers and elementary school students in digital literacy to master computers. The service was carried out through a zoom meeting with participants of elementary school teachers and students in the Semarang City area. Workshop activities began with analyzing training needs, determining the type of training, delivering materials, and evaluating through practice by participants. As a result, the participants' skills in using computers have improved from the previous one. The participants' understanding of computer operation, especially the use of automation in Microsoft Word, also increased.